Institusionalisasi Proses Mediasi dalam Sistem Peradilan di Indonesia - sri wardah (Fakultas Hukum Universitas Islam Indonesia, 2004)
The mediation process of intemalization in the judicature system which it is expected to strengthen and maximize the function of judicature Institution forming in judicial conflict solution and the function of the law strengthen and the justice managed through PERMA, in order that it can be improved effectively in the form of legislation.